Results Of The Early Eye Occlusion In Newly Preterm Very Low Weight And Its Relationship With Retinopathy Of Prematury - admin, admin (2018)
Objectives. A study was done to demonstrate if the ocular occlusion is related to the incidence of retinopathy in premature infants in the Maternal Perinatal Institute. Materials and methods.The analytical quasi-experimental study, includes all the premature babies of very low weight (<1301 grams.) and less than 32 weeks, born between January 01, 2005 to December 31, 2007. It was considered to be 201 patients who expired with the criteria of incorporation, they were divided in two groups, one of them whom became occlusion both eyes with mask of black fabric (study) and other one without occlusion exposed to the natural light of the environment (control). Results.The ROP’s incident was compared in both groups presenting some ROP’s degree 25 of 97 patients with eyes occluded (25,8 %) and 34 of 104 patients with eyes not occluded (32.7 %). Conclusions. It concludes that the occlusion does not diminish the incident to develop retinopathies in born premature babies of very low weight but it has protective effect in severe cases of this one disease.